2019
DOI: 10.1016/j.bbrep.2019.100657
|View full text |Cite
|
Sign up to set email alerts
|

Role of sunscreen formulation and photostability to protect the biomechanical barrier function of skin

Abstract: The impact of sunscreen formulations on the barrier properties of human skin are often overlooked leading to formulations with components whose effects on barrier mechanical integrity are poorly understood. The aim of this study is to demonstrate the relevance of carrier selection and sunscreen photostability when designing sunscreen formulations to protect the biomechanical barrier properties of human stratum corneum (SC) from solar ultraviolet (UV) damage. Biomechanical properties of SC samples were assayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…The exact mechanisms for these trends need further investigation and a study with a larger population is needed to achieve more statistical significance. However, the results of the present study are meaningful as the study mimicked the real life conditions of the skin 27 This is primarily due to the effects on the stratum corneum cell cohesion and mechanical integrity by alteration of intercellular lipids and corneodesmosomes. 28 A previous study regarding cumulative exposures to suberythemal dose demonstrated that cutaneous damages, such as the induction of sunburn cells, alteration of Langerhans cells, and active melanocytes, occur even without erythema formation.…”
Section: Discussionmentioning
confidence: 71%
“…The exact mechanisms for these trends need further investigation and a study with a larger population is needed to achieve more statistical significance. However, the results of the present study are meaningful as the study mimicked the real life conditions of the skin 27 This is primarily due to the effects on the stratum corneum cell cohesion and mechanical integrity by alteration of intercellular lipids and corneodesmosomes. 28 A previous study regarding cumulative exposures to suberythemal dose demonstrated that cutaneous damages, such as the induction of sunburn cells, alteration of Langerhans cells, and active melanocytes, occur even without erythema formation.…”
Section: Discussionmentioning
confidence: 71%
“…In that study, a decrease in DTI was associated with decrease in elastic modulus revealing alterations in the mechanical properties of the corneocytes, likely caused by reduced hydration leading to the shrinkage of the cornified envelope. Interestingly, Berkey et al showed that skin exposure to UVR caused decrease in the surface cohesion, this effect being reverted after treatment with an emollient or humectant. In concordance with the study of Berkey et al, showing alterations in mechanical properties of corneocytes after UVR, Engebretsen et al found elevated DTI levels on the cheek in participants who self‐reported higher exposure to sunlight.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Berkey et al showed that skin exposure to UVR caused decrease in the surface cohesion, this effect being reverted after treatment with an emollient or humectant. In concordance with the study of Berkey et al, showing alterations in mechanical properties of corneocytes after UVR, Engebretsen et al found elevated DTI levels on the cheek in participants who self‐reported higher exposure to sunlight.…”
Section: Discussionmentioning
confidence: 99%
“…Cosmetic products kwon as sunscreen are frequently used to prevent skin damage promoted by UV radiation 8 . The active ingredients of these products are called UV filters and are substances capable of absorbing, scattering or reflecting solar radiation.…”
Section: Introductionmentioning
confidence: 99%